Gray Zone in the Selection of Senior Executive Service Positions - Fattah, Sulaeman; Musdah, Erwin; Umar, Arif Alauddin (KnE Social Sciences, 2022)
The selection of senior executive service positions in Indonesia is carried out openly as part of the merit system. Although this policy has been in place for the past few years, senior executive service position selection in Indonesia still faces many obstacles. This research examined the process of each stage of the open selection process in Wajo and Pare-Pare. Qualitative methods were used with a case study approach. The main conclusion of this research was that there are still weaknesses in the open selection process, especially in the selection of senior executive service positions, where there is still a gray area. The absence of more specific standards regarding the selection process means that the selection committee has great power in determining the selection standards, particularly in terms of interviews and writing samples. The high percentage of evaluations for selections can mean that the acceptance of the participants is determined by the subjectivity of the selection committee. It was found that the selection process was not good enough to assess the competence of the selection participants. Although the selection process follows regulations, the results do not reflect the objective of the merit system, which is to recruit based on the skills of employees. Keywords: recruitment, open selection, senior executive service positions